Rice Marketing Supports The Improvement Of Farmers Welfare In Sukamaju Village Sunggal - Ocdy Amelia; Sulardi; Hardiansyah Putra; Muhammad Bahij Albaqy (Yayasan Multidimensi Kreatif, 2024)
This study aims to determine the increase in rice craftsmen's income, and the impact of regional and village productivity development, the sampling method is using Total Sample (census) is a data collection where the entire population is investigated without exception. All populations used as samples are 5 samples. The analysis method used is descriptive and SWOT Matrix. The success of increasing rice collectors' income can be realized if supported by the availability of good rice, the availability of tools and machines, and capital loans to collectors, where this study plays an active role in running and increasing the income of rice craftsmen's businesses. From the results of visits and interviews, the average value of rice craftsmen's business income in the research area was Rp. 8,171,500.-/month. This shows that business activities have a fairly moderate income in creating family welfare. The right SWOT strategy for rice craftsmen in Sunggal in developing their business and increasing their income is the Aggressive Strategy based on the SO strategy. The quality factor of the rice is a factor that can be utilized by Craftsmen in Sunggal to increase the selling price. So that the income received by the craftsmen's businesses will also increase and be sufficient to support their families.